ANALISIS SISTEM PENGENDALIAN INTERNAL ATAS SIKLUS PENDAPATAN (Studi Kasus Perusahaan Jasa Freight Forwarding di Jakarta) - Linda Rosyidah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
. The revenue cycle has a direct influence on the financial performance and operational sustainability of freight forwarding service companies. The main risks are associated with recording processes and their impact on cash flow, where delays or errors in billing and payment collection can significantly affect corporate liquidity. Effective internal control enables companies to detect and address problems more quickly, enhance operational efficiency, and reduce potential losses caused by errors or delays. This study evaluates and proposes improvements to internal control over the revenue cycle of Company X by applying the principles of the COSO framework. A qualitative approach with descriptive analysis through observation and interviews was employed. The findings reveal several weaknesses in internal control over the revenue cycle, particularly in organizational structure, segregation of duties, and reliance on manual communication, which limit the effectiveness of control mechanisms. Furthermore, risk assessment identified critical issues such as bad debts, operational disruptions, and recording errors that need to be managed appropriately to minimize negative impacts on company performance and to achieve a more efficient revenue cycle management.